Efficacy in treatment of subclinical cervical HPV infection without intraepithelial neoplasia: systematic review - Russomano, Fábio (2000)
CONTEXT: The treatment of the subclinical Human papillomavirus (HPV) infection of the uterine cervix is controversial. OBJECTIVE: To assess the efficacy of any therapy for subclinical HPV infection of the cervix without intraepithelial neoplasia, via a search in the medical literature. METHOD: We performed a systematic review with a comprehensive reference search in Medline, LILACS, Excerpta Medica, AIDSLINE, Popline, Cochrane Library and other authors' reference lists to identify experimental studies of therapy for subclinical HPV infection without intraepithelial neoplasia of the uterine cervix. In order to identify unpublished studies, we also contacted experts in the area, clinical trial registries, pharmaceutical industries, government and research institutions. We also searched on the Internet and in the book-of-abstracts of some medical conferences. The studies identified were masked and selected by inclusion criteria to help ascertain their internal validity. The data about regression or progression of HPV infection were extracted from the studies included. RESULTS: We identified 67 studies related to the treatment of subclinical HPV infection without intraepithelial neoplasia of the uterine cervix. Only five clinical trials matched the inclusion criteria and none demonstrated significant differences between the experimental group and the control group concerning regression of HPV infection (with or without CIN I) or progression to higher grades of CIN. CONCLUSION: The evidence we found in the medical literature regarding the efficacy of any therapy for subclinical HPV infection without intraepithelial neoplasia of the uterine cervix was unsatisfactory.